115k views
3 votes
What is the answer to this quation

What is the answer to this quation-example-1
User Dgorur
by
7.2k points

2 Answers

0 votes

Answer:

Step-by-step explanation:g(t)=t^2 - t

f(x) = (1 + x)

g(f(x)) = f(x)^2 - f(x)

g(f(x)) = (x + 1)^2 - x - 1

g(f(0)) = (0 +1)^2 - x - 1

g(f(0)) = 1 - 1 - 1 = -1

User Wilson Tran
by
7.4k points
4 votes

Answer:

Explanation:

g(t)=t^2 - t

f(x) = (1 + x)

g(f(x)) = f(x)^2 - f(x)

g(f(x)) = (x + 1)^2 - x - 1

g(f(0)) = (0 +1)^2 - x - 1

g(f(0)) = 1 - 1 - 1 = -1

================================

f(x) = 1 + x

f(g(t)) = 1 + g(t)

f(g(t)) = 1 + t^2 - t

f(g(0)) = 1 + 0 - 0

f(g(0)) = 1

The answer I'm getting is 0.

User Terry
by
7.1k points